2023
DOI: 10.1002/anie.202216917
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Zinc Homeostasis by a Novel Platinum(IV)‐Terthiophene Complex for Antitumor Immunity

Abstract: Zinc homeostatic medicine is of great potential for cancer chemo-immunotherapy; however, there are few reports on antitumor compounds that can trigger Zn 2 + -mediated immune responses. In this work, we developed a novel cyclometalated Pt IV -terthiophene complex, Pt3, that not only induces DNA damage and cellular metabolism dysregulation, but also disrupts zinc homeostasis as indicated by the abnormal transcriptional level of zinc regulatory proteins, excess accumulation of Zn 2 + in cytoplasm, and down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…38(a)) that can simultaneously perturb intracellular redox and Zn 2+ homeostasis to activate pyroptosis and immune responses including ICD, DC maturation and T cell tumor-infiltration. 249 As indicated in the above-mentioned section, the rhenium( i ) pyroptosis inducer 2-60 and the iridium( iii ) ferroptosis inducer 3-33 also feature ICD stimulation property. 109,245 At present, organometallic ICD inducers are still rare, and most of them were developed during the last three years and are mainly based on platinum( ii ), 258,260 gold( i ) 261,262 and iridium( iii ).…”
Section: Anti-tumor Organometallics Triggering Cell Death Pathwaysmentioning
confidence: 88%
See 1 more Smart Citation
“…38(a)) that can simultaneously perturb intracellular redox and Zn 2+ homeostasis to activate pyroptosis and immune responses including ICD, DC maturation and T cell tumor-infiltration. 249 As indicated in the above-mentioned section, the rhenium( i ) pyroptosis inducer 2-60 and the iridium( iii ) ferroptosis inducer 3-33 also feature ICD stimulation property. 109,245 At present, organometallic ICD inducers are still rare, and most of them were developed during the last three years and are mainly based on platinum( ii ), 258,260 gold( i ) 261,262 and iridium( iii ).…”
Section: Anti-tumor Organometallics Triggering Cell Death Pathwaysmentioning
confidence: 88%
“…In the meantime, along with membrane rupture, damage-associated molecular patterns (DAMPs) related to ICD and some To date, reports on metal-based complexes as pyroptosis inducers are quite limited. 109,249 Indeed, pyroptosis is often associated with immune responses such as ICD and the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway. As a DNA sensor, cGAS can be activated by both endogenous and exogenous DNA to produce the second messenger cyclic GMP-AMP (cGAMP), which can be detected by the cyclic-dinucleotide sensor STING, and subsequently evoke a strong type I interferon response that leads to innate anticancer immunity.…”
Section: Ferroptosis and Pyroptosismentioning
confidence: 99%
“…Capitalizing on this, there is a high demand for compounds that induce an immunogenic response inside the targeted cancer cells. 20,21 Among other strategies, chemotherapy-induced immunogenic cell death (ICD) may offer a general strategy to kill the tumor cells by eliciting broad antitumor immunity. 22 Previous studies [23][24][25][26][27][28][29] have demonstrated that Pt(II) and Pt(IV) complexes can cause ICD.…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis is an emerging programmed cell death with the characteristics of cell membrane rupture, continuous cell swelling, and leakage of intracellular proinflammatory mediators. During the pyroptosis process, the formation of inflammasomes activates the caspase 1 and pro-inflammatory cytokines (IL-1β and IL-18), and caspase-1 can cleave gasdermin D to release the N-terminal domain (GSDMD-N) which executes pyroptosis via its pore-forming activity. , To date, pyroptosis has attracted widespread concern in cancer therapy, and a variety of nanomaterials have been developed to elicit pyroptosis by photodynamic therapy, chemodynamic therapy, and so on. However, pyroptosis still inevitably suffers from setbacks arising from the intrinsic adaptive survival mechanism and treatment resistance of cancer cells. ,,,, Notably, recent studies have reported that autophagy may act as a checkpoint to negatively regulate pyroptosis, thus resulting in therapeutic resistance. …”
Section: Introductionmentioning
confidence: 99%